Lexicographical Study on the Verbal Aspect of the Matigsalug Language - Niñal, Norie I; Palma, Reita C. (Journal of Natural Language and Linguistics, 2024)
It cannot be denied that the Philippines is rich in language and culture. One of them is the Matigsalug language. This study focuses on the lexicography of the Matigsalug language focusing on the verb aspect. The main participants of this study are five selected Matigsalug who have skills and sufficient knowledge in speaking and writing the Filipino and Matigsalug languages. The instrument used in the research done is the translation of the list or table of words written in the Filipino language that are in the verb aspect. In this study, the researcher used a qualitative design and the ethnographic method of study that represents a broad research method and design to develop a dictionary. For a more extensive and meaningful interpretation and study of the data, the researcher used Descriptive Linguistics Analysis or descriptive language analysis. Based on the results of the study, it was proven that many verbs are used by the Matigsalug. There are additions to the perfective, imperfective and contemplative aspects, exchange of graphemes, use of hyphens, and writing and pronunciation methods in the Matigsalug lexicography. The implication of this study will help develop teachers’ understanding and guidance to Matigsalug students.